PENGARUH PROFESIONALISME, KOMPETENSI, INDEPENDENSI, DAN INTEGRITAS TERHADAP KUALITAS AUDIT APARAT INSPEKTORAT PROVINSI BALI - Susimartini, Made Widya; Yenni Latrini, Made (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.06.TAHUN.2023DO - 10.24843/EEB.2023.v12.i06.p10, 2023)
The inspectorate as the government's internal auditor has an important role as a monitoring function in achieving a governance, free from corruption, collusion, and nepotism. The quality of the audit is the basis for the assessment in the supervision that has been carried out by the inspection. The purpose of this study is to determine the effect of professionalism, competence, independence, and integrity on audit quality, using an associative quantitative approach. The population in this study was 61 people. The research sample was 61 officials as internal auditors at the Bali Provincial Inspectorate Office, using purposive sampling methods. For the analysis technique used is multiple regression linear. The results of this study indicate that the variables of professionalism, competence, independence, and integrity have a positive effect on the quality of the audit, so that the higher the professionalism, competence, independence, and integrity of the auditor, for better quality of the audit produced, and will affect in the next audit assignment, so that later the quality of the audit produced is more qualified and trusted.